Elevated free secretory component in early rheumatoid arthritis and prior to arthritis development in patients at increased risk. (27th August 2019) - Martinsson, Klara; Roos Ljungberg, Karin; Ziegelasch, Michael; Cedergren, Jan; Eriksson, Per; Klimovich, Vladimir; Reckner, Åsa; Griazeva, Irina; Sjöwall, Christopher; Samoylovich, Marina; Skogh, Thomas; Wetterö, Jonas; et al.
Abstract: Objectives: Considering growing evidence of mucosal involvement in RA induction, this study investigated circulating free secretory component (SC) in patients with either recent-onset RA or with ACPA and musculoskeletal pain. Methods: Two prospective cohorts were studied: TIRA-2 comprising 452 recent-onset RA patients with 3 years of clinical and radiological follow-up, and TIRx patients ( n = 104) with ACPA IgG and musculoskeletal pain followed for 290 weeks (median). Blood donors and three different chronic inflammatory diseases served as controls. Free SC was analysed by sandwich ELISA. Results: Serum levels of free SC were significantly higher in TIRA-2 patients compared with TIRx and all control groups ( P < 0.01). Among TIRx patients who subsequently developed arthritis, free SC levels were higher compared with all control groups ( P < 0.05) except ankylosing spondylitis ( P = 0.74). In TIRA-2, patients with ACPA had higher baseline levels of free SC compared with ACPA negative patients ( P < 0.001). Free SC status at baseline did not predict radiographic joint damage or disease activity over time. In TIRx, elevated free SC at baseline trendwise associated with arthritis development during follow-up ( P = 0.066) but this disappeared when adjusting for confounders ( P = 0.72). Cigarette smoking was associated with higher levels of free SC in both cohorts. Conclusion: Serum free SC levels are increased in recent-onset RA compared with other inflammatory diseases, and associate with ACPA and smoking. Free SC is elevated before arthritis development among ACPA positive patients with musculoskeletal pain, but does not predict arthritis development. These findings support mucosal engagement in RA development.